I've got my eyes on you [large type] : a novel - Clark, Mary Higgins (Thorndike Press, a part of Gale, a Cengage Company, 2018)
After a party when her parents are away, eighteen-year-old Kerry Dowling is found fully dressed at the bottom of the family pool. The immediate suspect is her boyfriend who had a bitter argument with her at the party. Then there is a twenty-year-old neighbor who was angry because she didn't invite him to the party. Or is there someone else who has not yet been seen on the radar? Kerry's older sister Aline, a twenty-eight-year-old guidance counselor, is determined to assist the Prosecutor's Office in learning the truth. She does not realize that now she is putting her own life in danger...